Makna Kata Anuq dalam Bahasa Sasak di SMP Negeri 2 Batukliang Utara - Hollysa Andini; Mahyuni Mahyuni; Nuriadi Nuriadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
This research is aimed at describing the meaning of the word “anuq” which is commonly spoken by Sasak people in SMP Negeri 2 Batukliang Utara using semantics theory. The source of data were the conversations among teachers and administrators of SMP Negeri 2 Batukliang Utara. The data were collected by applying listening, speaking, and introspection method. The result of the research showed that the word “anuq”has many meanings based on the context or topics of the communication. Sasak people in SMP Negeri 2 Batukliang Utara basically used “anuq” when the speaker forgot or lost the word to be spoken.